2018
DOI: 10.1111/srt.12459
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent skin texture analysis and evaluation using mobile camera image

Abstract: The proposed method in this study shows that the skin surface can be quantitatively evaluated by the similarity with ground truth. We also propose a method to diagnose and manage individual skin condition using a mobile camera in real life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…In addition to being cost-effective and highly usable and having excellent hardware, mobile phones are capable of obtaining high-resolution images anywhere and at any time, thus being useful in various fields of study, particularly biometrics [9,10]. Through our prior study [11], we confirmed a high-performance mobile camera can acquire a high-resolution close-up image that can be observed at up to a micrometer resolution.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…In addition to being cost-effective and highly usable and having excellent hardware, mobile phones are capable of obtaining high-resolution images anywhere and at any time, thus being useful in various fields of study, particularly biometrics [9,10]. Through our prior study [11], we confirmed a high-performance mobile camera can acquire a high-resolution close-up image that can be observed at up to a micrometer resolution.…”
Section: Introductionmentioning
confidence: 56%
“…Additionally, prior studies on skin surface analysis performed research by selecting the region of the skin with a small distortion effect on the skin image, thus having a limitation in the observation region. To overcome this limitation, the proposed fine distortion correction method enables us to use the entire region of the mobile image and observe regions about eight times wider than the existing skin observation region [ 11 ]. The proposed correction distortion method, DCM, can be utilized and applied for the correction of various kinds of camera lens distortion.…”
Section: Discussionmentioning
confidence: 99%
“…The range of disease is expanding; it becomes difficult to distinguish the boundaries between the disease and the surrounding normal skin (4th column). These become factors that make accurate segmentation difficult 21 . All four algorithms generally perform accurate segmentation, even with challenging images.…”
Section: Resultsmentioning
confidence: 99%
“…However, a specialized equipment is challenging to use and expensive. Therefore, in our previous study, we acquired unconstrained skin images using a mobile device and conducted a skin microstructure analysis of the mobile images [8][9][10][11]. However, the analysis of the skin microstructure was difficult for topological changes such as blood vessels appearing prominently on the skin surface in the mobile images.…”
Section: Introductionmentioning
confidence: 99%